Pemanfaatan Online Food Delivery (Shopee Food Dan Gofood) Dalam Pemasaran Dan Penjualan Produk UMKM Di Gunung Anyar Tambak - Shinta Rifianing Prasetya; Rafi Athallah Rivai; Muhammad Bagus Yoga Hutama; Dimas Aditya Rama; Dyan Fransiska Agata (CV. Aksara Global Akademia, 2023)
Along with the current technology development, business activities in the culinary field also use technology to run their business. One of them is the use of online food delivery services which is no longer an advantage of a business today but has become a necessity for business owners to compete with other companies. The implementation of this community service aims to facilitate MSMEs to have skills in the use of online food delivery technology, especially using GoFood and Shop Food to market their products. This research uses descriptive qualitative methods by conducting observations and interviews, not only that, this research uses the learning method of practicing using online food delivery technology. The result of this community service is that MSMEs can market their products through GoFood and Shop Food so that the marketing range will be more comprehensive and attract more consumers, which can also increase sales